PROBLEMS FACED BY WORKING WOMEN: A SOCIOLOGICAL STUDY OF NURSES IN PRIVATE SECTOR - Chaudhary, Reena; Amrita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Even in this competitive world, nurses as professionals view caring for their patients as their moral obligation and regard their job as selfless service. All this demands a lot of patience, commitment and dedication from nurses. Although nursing has been a popular choice of career among youth, yet there has been demand and supply mismatch which perpetuates global scarcity of nurses. This inadequate number of nurses and the resulting fewer employed nurses face work overload which ultimately leads to emergence of a variety of problems faced by them. The present paper seeks to explore the various problems faced by nurses working in private hospitals in S.A.S. Nagar district of Punjab (India). For the purpose of analysis, the problems of nurses have been studied at three levels: at workplace, at familial level and at societal level. The study concludes that remuneration and hospital policies was problem faced at workplace, stress at familial level and limited social interaction at societal level.